Intensity of community-based programs by long-term care insurers and the likelihood of frailty: Multilevel analysis of older Japanese adults. (January 2020) - Sato, Koryu; Ikeda, Takaaki; Watanabe, Ryota; Kondo, Naoki; Kawachi, Ichiro; Kondo, Katsunori
Abstract: The World Health Organization (WHO) argues that governments can postpone declining capacity of older adults by providing sufficient support. Yet, to our knowledge, no study has focused on the role of local governments for realizing healthy ageing. This study examined the association between the intensity of community-based programs for frailty postponement by long-term care insurers (as municipalities) and the likelihood of frailty. We analyzed repeated cross-sectional data of three waves (2010-11, 2013, and 2016) from the Japan Gerontological Evaluation Study (JAGES). Participants included 375, 400 older adults aged 65 years or older (M = 74.1) living in a total of 81 regions covered by insurers in Japan. Frailty was assessed by a governmental standardized index, the Kihon Check List (KCL; a basic function check list in Japanese). Estimations were obtained using a multilevel logistic model with random slopes. We found that every social activity per hundred older people organized by a long-term care insurer was significantly associated with an 11% reduction of the likelihood of frailty (Odds ratio = 0.89; 95% credible interval = 0.81, 0.99). Although the main effect of educational events was not significant, the point estimate was slightly larger for people with lower levels of education than for those with higher education. The results also suggested that insurer-organized social activities could be more beneficial in communities with few opportunities for civic participation. The variation in intensity of community-based programs by long-term care insurers may explain part of a disparity in the likelihood of frailty between municipalities. Highlights: First study exploring community-based programs' intensity by insurers and frailty. One social activity per 100 people was associated with reduced frailty of 11%. Educational events were more effective among people with lower levels of education. Interventions were more beneficial in communities with inadequate social capital.